Students' perspectives of factors related to delayed completion of online RN-BSN programs - Kechinyere C. Iheduru-Anderson (BMC, 2021)
Abstract Background There are multiple educational programs for individuals to become registered nurses (RNs), and the transition from an associate degree or diploma to a Bachelor of Science in Nursing (BSN) degree is vital to healthcare. This study examined the factors contributing to delayed completion or withdrawal from online RN-BSN nursing programs from students' perspectives. Method Thematic content analyses were conducted on qualitative data obtained from semi-structured interviews (N = 26). Results Complex factors contributed to delayed completion of online RN-BSN programs, including student-, institutional-, and faculty-related factors. Conclusion This study validated and extends previous studies without delineating students in fully online programs from hybrid and face-to-face programs. Students, faculty, and institutions all have a role to play in facilitating on-time program completion. Recognizing and mitigating the barriers that delay on-time program completion is required to foster nurses to obtain a BSN degree.